Investigation of Coastal Atmospheric Boundary Layer and Particle by Unmanned Aerial Vehicle under Different Land-sea Temperature - Yingxiao Tang; Xu Yang; Jianbo Yang; Ziying Cai; Suqin Han; Jing Shi; Ming Jiang; Yulu Qiu (Aerosol and Air Quality Research)
Abstract During summer daytime, the surface PM2.5 concentration tends to rise briefly in the west coast of Bohai Sea, which might be related to the thermal internal boundary layer (TIBL) formed by the land-sea thermal interaction. In this study, we investigated the relationship between land-sea air temperature and pollutant concentration in summer over a coastal region of northern China using an unmanned aerial vehicle (UAV)-measurement platform to obtain vertical meteorological data and pollutant concentration. In midday, when only considered onshore winds, PM2.5 concentration was significantly higher than that in not considered onshore winds, meanwhile the high positive correlation between land-sea temperature difference and particle concentration was identified. It can be seen from the UAV observed profiles that the TIBLs were formed at the bottom of the atmospheric layer in the daytime with height values in the range of 44–97 m, resulting from the impact of onshore winds caused by land-sea thermal difference. This land-sea thermal difference influences the atmospheric boundary layer (ABL) and TIBL structures, also the PM2.5 concentration diffusion. We found that larger land-sea temperature difference could induce lower coastal ABL height and larger potential temperature vertical gradients below TIBL, even delaying the stable layer establishment. When TIBL and ABL heights increased, as a result, the height of the maximum PM2.5 concentration also increased. In addition, TIBL could lead to an increase in surface PM2.5 concentration lasting for 2 hours during the daytime. Our results establish the relationship between land-sea temperature difference and particle diffusion, and have an important role in coastal air quality forecast.